Direct Numerical Simulations of Turbulent Flow in Helical Pipes - Lupi, V.; Örlü, R.; Schlatter, P. (Springer Science and Business Media B.V., 2024)
Direct numerical simulations of the fully developed turbulent flow through helical pipes are performed. The numerical procedure is described, and a validation of the volume force driving the flow is presented. A comparison of the turbulence statistics against literature data is also reported.
CRIS-Team Scopus Importer:2023-12-08